The Circuits of Anti-Communist Repression between Asia and Latin America during the Second Cold War : Paraguay and the World Anti-Communist League - Bohoslavsky, Ernesto (2020)
Fil: Bohoslavsky, Ernesto. Universidad Nacional de General Sarmiento. Instituto del Desarrollo Humano; Argentina.